Rapid Resolution of Donor‐Derived Glomerular Fibrin Thrombi After Deceased Donor Kidney Transplantation. Issue 3 (21st December 2015) - Batra, R. K.; Heilman, R. L.; Smith, M. L.; Thomas, L. F.; Khamash, H. A.; Katariya, N. N.; Hewitt, W. R.; Singer, A. L.; Mathur, A. K.; Huskey, J.; Chakkera, H. A.; Moss, A.; et al.
Abstract : The aim of this study was to determine the clinical and histologic outcomes related to transplanting kidneys from deceased donors with glomerular fibrin thrombi (GFT). We included all cases transplanted between October 2003 and October 2014 that had either a preimplantation biopsy or an immediate postreperfusion biopsy showing GFT. The study cohort included 61 recipients (9.9%) with GFT and 557 in the control group without GFT. Delayed graft function occurred in 49% of the GFT group and 39% in the control group (p = 0.14). Serum creatinine at 1, 4, and 12 months and estimated GFR at 12 months were similar in the two groups. Estimated 1‐year graft survival was 93.2% in the GFT group and 95.1% in the control group (p = 0.22 by log‐rank). Fifty‐two of the 61 patients in the GFT group (85%) had a 1‐month protocol biopsy, and only two biopsies (4%) showed residual focal glomerular thrombi. At the 1‐year protocol biopsy, the prevalence of moderate to severe interstitial fibrosis and tubular atrophy was 24% in the GFT group and 30% in the control group (p = 0.42). We concluded that GFT resolves rapidly after transplantation and that transplanting selected kidneys from deceased donors with GFT is a safe practice. Abstract : Deceased donor kidneys with glomerular fibrin thrombi can have excellent graft survival, as fibrin thrombi resolve by one month in most cases without any deleterious effect on renal function or biopsy findings at one year.